The Analisis implementasi model Problem Based Learning (PBL) dalam Mengembangkan Kemampuan Berpikir Kritis Peserta Didik - Arina Hidayati, Ayu; Denok Mugi Hidayanti; Neviyani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Economic learning activities are often carried out to not only memorize concepts, but also understand, criticize, and apply them in real situations. This is done by analyzing data, making decisions in diagnosing problems, and understanding the impact or solution of a problem by students. The research has the following intentions: 1) to know the problem analysis using the Problem Based Learning (PBL) model to develop students' critical thinking skills in Economics class X IIS, 2) to know the problem diagnosis using the Problem Based Learning (PBL) model to develop students' critical thinking skills in economics class X IIS, and 3) to know alternative solutions using the Problem Based Learning (PBL) model to develop students' critical thinking skills in economics class X IIS. In the process, researchers used descriptive qualitative methods involving class X IIS at SMA Negeri 1 Rogojampi Banyuwangi. The data obtained are as follows. 1) problem analysis is carried out using the information search method by checking between opinions and facts, determining real ideas from their own thoughts related to payment systems and tools, both cash and non-cash. 2) Problem diagnosis is carried out in two stages, namely the assessment of the factors that cause the problem and the consequences that occur when there is a problem. 3) Determination of alternative solutions using the PBL model is done by analyzing payment systems and tools in real situations and constructing facts with opinions.